Outcome of Children With Acute Encephalitis and Refractory Status Epilepticus. (December 2014) - Sasaki, Jun; Chegondi, Madhurandhar; Raszynski, Andre; Totapally, Balagangadhar R.
Acute encephalitis in children is a life-threatening neurological emergency. However, little is reported about the outcome of this devastating illness in the United States. The authors retrospectively reviewed the charts of patients admitted to a regional pediatric intensive care unit with the diagnosis of acute encephalitis between 2006 and 2011. In 41 cases that met the inclusion criteria, the most common presenting symptoms were fever (65.9%), altered mental status (61%), and seizures (58.5%). Eight patients (19.5%) who presented with refractory status epilepticus had a longer median length of stay in the pediatric intensive care unit (46 vs 4 days; P < .0001) and a significant worsening of Pediatric Cerebral Performance Category score on discharge by 2 or more points (odds ratio 20.38; 95% confidence interval, 2.89-143.52). All children survived to hospital discharge. In conclusion, children with acute encephalitis who present with refractory status epilepticus have a worse neurological outcome and a longer stay in the pediatric intensive care unit.